1999
DOI: 10.1111/j.1469-7793.1999.343ae.x
|View full text |Cite
|
Sign up to set email alerts
|

A rise in intracellular Ca2+ underlies light adaptation in dogfish retinal ‘on’ bipolar cells

Abstract: The rod visual system is extraordinary not only in its great sensitivity in the dark-adapted state, when it is capable of the detection of a few photons, but also in its ability to operate over a range of light intensities about a million times greater than absolute threshold (Aguilar & Stiles, 1954). High sensitivity in the dark-adapted state is achieved by high gain in phototransduction in rods (Pugh & Lamb, 1993) and in synaptic transduction in 'on' bipolar cells (Shiells & Falk, 1994), each involving a cGM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
39
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 23 publications
12
39
0
Order By: Relevance
“…Sodium channels in transient bipolar cells enhanced the peak-tosustained response index, whereas the index of sustained bipolar cells was not affected by TTX, suggesting sodium channels selectively boosted the transient response component. Nawy (2000) and Shiells and Falk (1999) suggested that the calciumdependent desensitization of the mGluR6-gated channels shapes the transient response component of ON bipolar cells. Our observation that sodium currents shape transient responses is probably an independent mechanism, because BAPTA (10 mM), which was present in our intracellular solution, blocks calciumdependent desensitization (Nawy, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Sodium channels in transient bipolar cells enhanced the peak-tosustained response index, whereas the index of sustained bipolar cells was not affected by TTX, suggesting sodium channels selectively boosted the transient response component. Nawy (2000) and Shiells and Falk (1999) suggested that the calciumdependent desensitization of the mGluR6-gated channels shapes the transient response component of ON bipolar cells. Our observation that sodium currents shape transient responses is probably an independent mechanism, because BAPTA (10 mM), which was present in our intracellular solution, blocks calciumdependent desensitization (Nawy, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, glutamate release and/or mGluR6 signaling could have been affected in dfw 2J retinas. Although the kinetics of exocytosis and synaptic depression appear to be similar in rods and cones (Kreft et al, 2003;Rabl et al, 2006), the neurotransmission at cone synapses is significantly faster (Schnapf and Copenhagen, 1982;Cadetti et al, 2005 (Shiells and Falk, 1999;Berntson et al, 2004;Nawy, 2004). Elevated [Ca 2ϩ ] i would, in turn, "adapt" rod bipolar responses to light stimulation, accounting for the loss of sensitivity observed in ERG and single-cell recordings.…”
Section: Pmca2 Modulates Synaptic Transmission At Rod Synapsesmentioning
confidence: 99%
“…3) (Sakai et al, 1995;Smirnakis et al, 1997). Second, Ca 2ϩ -dependent mechanisms in the dendrites of ON bipolar cells contribute to mean but not contrast adaptation (Shiells and Falk, 1999) (Fig. 10).…”
Section: Mean and Contrast Adaptation In The Retinamentioning
confidence: 99%
“…3) indicates that contrast adaptation is mediated after signals are transferred to the bipolar cell. The experiments described below tested several possible mechanisms: (1) voltageactivated conductances in the bipolar soma (Mao et al, 1998); (2) amacrine feedback to the bipolar synaptic terminal (Maguire et al, 1989); (3) horizontal cell input to the bipolar dendrites (Mangel, 1991); and (4) Ca 2ϩ -dependent mechanisms in the bipolar dendrites (Shiells and Falk, 1999;Nawy, 2000).…”
Section: Mechanism Of Contrast Adaptation In Bipolar Cellsmentioning
confidence: 99%
See 1 more Smart Citation